Evaluation of Maintenance and Drainage Damage Factors on the Condition of the Kadipaten - Jatiwangi Road (PT. Gistek Indonesia S.D. Bridge 2 Cisambeng) - Ari Ayu Arimba; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2024)
Drainage is of course one of the most necessary aspects of the road component, and we should pay more attention to this aspect, and we also need to know that one of the causes of damage to a road is due to damage or non-functioning drainage. So the purpose of this case study is to identify road drainage problems that are on the Kadipaten road to Jatiwangi along 2,951 m from the front of PT Gistex Indonesia to the Cisambeng 2 bridge, which in the sector of the route is the industrial sector, lots of factory building growth right on the side national roads in the district. Majalengka, knowing how crowded and congested the national roads are. From the results of the observation of this case study, it can be concluded that there are still many inactive or disconnected canals, sediment, garbage, and large stones that have accumulated and clogged the drainage. then there is an STA Drainage point right in front of PT. LYG, you can say the worst condition is where the DPT drainage wall has collapsed. A good design needs to be done knowing that the drainage construction has not been done in 1 year.